THE EFFECT OF COMPANY SIZE, DEBT TO EQUITY RATIO, AND RETURN ON EQUITY RATIO ON DIVIDEND PAYOUT RATIO IN FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FROM 2019 TO 2024 - Azzahra Talitha Noer Nanlohy; Niswatin; Yustina Hiola (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effect of company size, Debt to Equity Ratio (DER), and Return on Equity (ROE) on the Dividend Payout Ratio (DPR) of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2024. This research adopts a quantitative approach with multiple linear regression analysis processed using SPSS. The sample of the study consists of 18 companies that meet the purposive sampling criteria. The results show that company size has a positive and significant effect on the Dividend Payout Ratio. However, Debt to Equity Ratio and Return on Equity do not have a significant effect on Dividend Payout Ratio, either partially or simultaneously. These findings suggest that other factors, beyond company size, play a more significant role in influencing dividend policies in the food and beverage manufacturing sector in Indonesia.